2022
DOI: 10.1007/s10964-022-01604-6
|View full text |Cite
|
Sign up to set email alerts
|

Minority and Majority Adolescents’ Attitudes toward Mutual Acculturation and its Association with Psychological Adjustment

Abstract: Although acculturation is considered a mutual process, no measure assesses attitudes toward mutual acculturation. Through a novel four-dimensional measurement, this study addresses this research gap by assessing attitudes toward minority and majority acculturation and its relation to psychological adjustment for immigrant-background minority and non-immigrant majority adolescents in public secondary schools in three European countries: in Germany (n = 346, 46% female, Mage = 12.78 years, range 11–16), Greece (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Finally, the cultural distancing profile demonstrated a tendency to agree with the heritage culture maintenance dimension and a tendency to disagree with the dominant culture adoption dimension and disagreement with both majority dimensions. The three profiles found in this study resemble the three profiles found in the first year of the longitudinal data collection (Sidler et al, 2022 ), showing only a slight variation in the cultural distancing profile in terms of shifting from disagreement to agreement concerning migration background students' heritage culture maintenance.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Finally, the cultural distancing profile demonstrated a tendency to agree with the heritage culture maintenance dimension and a tendency to disagree with the dominant culture adoption dimension and disagreement with both majority dimensions. The three profiles found in this study resemble the three profiles found in the first year of the longitudinal data collection (Sidler et al, 2022 ), showing only a slight variation in the cultural distancing profile in terms of shifting from disagreement to agreement concerning migration background students' heritage culture maintenance.…”
Section: Discussionsupporting
confidence: 74%
“…This study was aimed at assessing whether adolescents differ in their mutual acculturation attitudes based on their national self-identification as being Swiss and/or having a migration background. Whereas, mutual acculturation attitudes have already been assessed in the school context (Sidler et al, 2022 ), how adolescents' self-identification relates to these mutual acculturation attitudes presented a research gap. Self-identification measures are key because in defining individuals' categorization in relation to ongoing norms of national belonging, researchers implicitly play a role in defining belonging and otherness (Moffitt and Juang, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, several public elementary schools in Kawaguchi host a large number of children whose parents moved to Japan as asylum-seekers. Research is limited on acculturation in school settings where ample intercultural interaction takes place between majority and minority group members (Sidler et al, 2022). Particularly, no majority-group acculturation research has explored the experiences of teachers as majority-group members and their interactions with children of asylum-seekers within Japanese school settings.…”
Section: Introductionmentioning
confidence: 99%